2004
DOI: 10.1097/01.brs.0000142433.21912.0d
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Disc Herniation and Epidural Gas: Something More Than a Casual Association?

Abstract: The potential presence of an intradural disc herniation must always be considered when performing an open discectomy on a patient whose CT scan study shows the presence of epidural gas. This association is particularly striking given the relative rarity of intradural herniations and intraspinal gas. In the event that no clear disc herniation was found, an intradural examination may be indicated to justify clinical signs and symptoms or previous radiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 48 publications
1
51
0
3
Order By: Relevance
“…2,3,7 Such adhesions may be congenital or develop after previous spinal surgery or trauma due to scar tissue formation. 7,8 In the present case, intradural LDH occurred subsequent to a dural tear during PELD, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…2,3,7 Such adhesions may be congenital or develop after previous spinal surgery or trauma due to scar tissue formation. 7,8 In the present case, intradural LDH occurred subsequent to a dural tear during PELD, which has not been previously reported.…”
Section: Discussionsupporting
confidence: 47%
“…Hidalgo-Ovejero et al reported that the potential presence of intradural LDH must always be considered when performing open discectomy in cases in which CT shows the presence of epidural gas. 8 Several authors have reported that MRI is the most useful imaging modality in cases of intradural LDH. Characteristic findings are the loss of PLL continuity and the "hawk-beak" sign, which shows a triangular aspect of the herniated disc compressed laterally.…”
Section: Discussionmentioning
confidence: 99%
“…The herniated discs appear as homogeneously isointense lesions on T1-and T2-weighted images. Hidalgo-Ovejero et al [16] pointed out the significance of gas within the spinal canal, which was associated with intradural disc herniations. Hida et al [17] stressed the usefulness of gadolinium-enhanced MRIs in making an accurate diagnosis preoperatively by showing a beak-like mass with ring enhancement at the level of the intervertebral space, which pointed to the abrupt loss of continuity of the PLL.…”
Section: Discussionmentioning
confidence: 99%
“…13,19) Disk degeneration is intimately related to the vacuum phenomenon, which is relatively common in old age. The gas associated with the vacuum phenomenon has been found in the spinal canal, intervertebral foramen, epidural space, and subarachnoid space, 8,17) but disk herniation with gas has rarely been reported. The majority of these cases have been the result of nonoperative treatments.…”
Section: Introductionmentioning
confidence: 99%